2024
DOI: 10.1186/s12870-023-04701-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of resistance to gray leaf spot by genome-wide association study in a multi-parent maize population

Can Hu,
Tianhui Kuang,
Ranjan K. Shaw
et al.

Abstract: Background Understanding the genetic mechanisms underlying gray leaf spot (GLS) resistance in maize is crucial for breeding GLS-resistant inbred lines and commercial hybrids. Genome-wide association studies (GWAS) and gene functional annotation are valuable methods for identifying potential SNPs (single nucleotide polymorphism) and candidate genes associated with GLS resistance in maize. Results In this study, a total of 757 lines from five recombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…The inbred line YML226 was selected from the CATETO related germplasm originating from tropical regions in Brazil and Argentina (Fan et al 2018 ). Hu et al ( 2024 ) demonstrated that YML226 showed high resistance to maize gray spot disease. Subedi et al ( 2015 ) conducted a survey of maize lines used in Nepal and found that maize derived from the CATETO germplasm imported from Yunnan Province, China showed high leaf spot resistance and yield.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inbred line YML226 was selected from the CATETO related germplasm originating from tropical regions in Brazil and Argentina (Fan et al 2018 ). Hu et al ( 2024 ) demonstrated that YML226 showed high resistance to maize gray spot disease. Subedi et al ( 2015 ) conducted a survey of maize lines used in Nepal and found that maize derived from the CATETO germplasm imported from Yunnan Province, China showed high leaf spot resistance and yield.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the tropical maize germplasm retained more favorable variations during domestication, conferring stronger resistance to diseases than temperate maize. The CATETO germplasm, originating in South America, has been proven to exhibit high general combining ability and disease resistance in both temperate and tropical-subtropical environments, thus, it has been widely used in breeding programs (Santos et al 2001 ; Subedi 2015 ; Fan et al 2018 ; Hu et al 2024 ). Therefore, identifying NLB resistant genes against maize NLB in populations derived from the tropical germplasm may be a good strategy for marker-assisted breeding.…”
Section: Introductionmentioning
confidence: 99%